Development of an Omnidirectional Walk Engine for Soccer Humanoid Robots. (29th December 2015) - Snafii, Nima; Abdolmaleki, Abbas; Lau, Nuno; Reis, Luis Paulo
Humanoid soccer robots must be able to carry out their tasks in a highly dynamic environment which requires responsive omnidirectional walking. This paper explains a new omnidirectional walking engine for a humanoid soccer robot that mainly consists of a foot planner, a zero moment point (ZMP) trajectory generator, a centre of mass (CoM) calculator and an active balance feedback loop. An analytical approach is presented for generating the CoM trajectory, in which the cart-table motion of the equations is solved using the Fourier approximation of the ZMP. With this approach, we propose using a new time segmentation approach in order to parametrize the double-support phase. An active balance method is also proposed which keeps the robot's trunk upright when faced with environmental disturbances. The walking engine is tested on both simulated and real NAO robots. Our results are encouraging given the fact that the robot performs favourably, walking quickly and in a stable manner in any direction in comparison with the best RoboCup 3D soccer simulation teams for which the same simulator is used. In addition, the proposed analytical Fourier-based approach is compared with the well-established numerical ZMP dynamics control method. Our results show that the presented analytical approach involves less time and complexity and better accuracy compared with the ZMP preview control method.